Lifestyle Modifications for Peripheral Arterial Disease Prevention in Type 2 Diabetes Mellitus Patient - Nurhadijah, Sitti; Chen, Hsing-Mei (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Lifestyle modifications like exercise, a healthy diet, and smoking cessation are crucial for Peripheral Arterial Disease (PAD) prevention in Type 2 Diabetes Mellitus (T2DM). Regular exercise enhances insulin sensitivity, improves blood circulation, and reduces PAD symptoms. A healthy diet with low glycemic index foods, fiber-rich vegetables, whole grains, and healthy fats stabilizes blood sugar levels, reduces LDL cholesterol, and slows PAD progression. Smoking cessation improves vascular health, reduces inflammation, and lowers the risk of PAD.